2015
DOI: 10.1590/1809-4392201400974
|View full text |Cite
|
Sign up to set email alerts
|

Parasitismo em tambatinga (Colossoma macropomum x Piaractus brachypomus, Characidae) cultivados na Amazônia, Brasil

Abstract: RESUMOOs estudos sobre os parasitos e doenças parasitárias são de grande interesse para a piscicultura, uma vez que podem afetar o crescimento dos peixes. O objetivo deste estudo foi investigar a fauna parasitária e relação parasito-hospedeiro em Colossoma macropomum x Piaractus brachypomus (tambatinga) de 10 pisciculturas do estado do Amapá, Amazônia. Parasitism in tambatinga (Colossoma macropomum x Piaractus brachypomus, Characidae) farmed in the Amazon, Brazil ABSTRACTThe studies on parasites and parasitic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 17 publications
1
27
1
10
Order By: Relevance
“…macropomum × ♂Piaractus brachypomus Cuvier) and the hybrid tambacu (4.4%) (♀C. macropomum × ♂Piaractus mesopotamicus Holmberg) from Amapá (Dias et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…macropomum × ♂Piaractus brachypomus Cuvier) and the hybrid tambacu (4.4%) (♀C. macropomum × ♂Piaractus mesopotamicus Holmberg) from Amapá (Dias et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In the Amazon region, some authors (ARAÚJO et al, 2009;MARINHO et al, 2013;DIAS et al, 2015;SILVA et al, 2016) have reported that high prevalence of parasites in fish farms was associated with low levels of dissolved oxygen in the water, high temperatures and inadequate sanitary conditions. These authors also reported that replenishing the breeding areas with water from natural environments also influenced occurrences and levels of infection.…”
Section: Discussionmentioning
confidence: 99%
“…High individual values for K n , an indicator of fish health, were obtained for P. brachypomus with low levels of parasitic intensity by Neoechinorhynchus sp. These results were similar to what was obtained for the tambatinga hybrid C. macropomum x P. brachypomus (Dias et al, ), parasitised at low densities by N. buttnerae and higher densities by Ichthyophthirius multifiliis , Piscinoodinium pillulare, and Monogenoidea. In a study on the parasite infracommunity in cage‐reared rainbow trout Oncorhynchus mykiss (Walbaum 1792), which was strongly dominated by Pomphorhynchus laevis , no significant influence of acanthocephalans on fish condition was found (Çevrimel & Soylu, ).…”
Section: Discussionmentioning
confidence: 99%